YouTube as a Platform for Promoting Digital Works: A Study on Ndarboy Genk Music Group Yogyakarta - Muhammad Panji Wahyu Mukti; Muhammad Jazuli; Syakir Syakir (Universitas Negeri Medan, 2023)
YouTube is the world’s largest video platform and has become a popular place for musicians to promote their digital music. This study aims to describe the effectiveness of YouTube as a platform to promote digital music by the music group Ndarboy Genk. The method used is descriptive-qualitative, describing Ndarboy Genk musicians who have used YouTube to promote their digital music. The perspective used to study this research is Internet marketing. Internet marketing is the process of empowering musicians to promote their websites, products, or services online and through social media channels to communicate with a much larger community. The result is that the YouTube digital platform is a solution for artists or music creators to promote their work without having to be sheltered by a music label; even music labels can be created by the artists or creators themselves.